Efficacy of sodium hypochlorite in overcoming antimicrobial resistance and eradicating biofilms in clinical pathogens from pressure ulcers - Fabrizio, Giorgia; Sivori, Francesca; Cavallo, Ilaria; Truglio, Mauro; Toma, Luigi; Sperati, Francesca; Francalancia, Massimo; Obregon, Francisco; Pamparau, Luisa; Kovacs, Daniela; Pimpinelli, Fulvia; Di Domenico, Enea Gino (Frontiers in Microbiology, 2024)
Sodium hypochlorite (NaOCl) is an antimicrobial agent for skin wound care, recognized for its broad-spectrum antimicrobial efficacy. This study investigates the effectiveness of NaOCl against 20 bacterial isolates, including carbapenem-resistant Klebsiella pneumoniae (CRKP), multidrug-resistant Acinetobacter baumannii (MDRAB), methicillin-resistant (MRSA) and -susceptible Staphylococcus aureus (MSSA), and 5 Candida albicans isolates from pressure ulcer (PUs) patients.Antibiotic resistance was prominently observed, with CRKP and MDRAB showing resistance to fluoroquinolones and carbapenems, while MRSA displayed resistance to β-lactams and levofloxacin. MSSA exhibited a comparatively lower resistance profile. Whole-genome sequencing pinpointed specific resistance genes, with CRKP and MDRAB harboring significant numbers of antimicrobial resistance genes (ARGs) while showing fewer disinfectant resistance genes (DRGs) than MRSA and MSSA. Notably, there was a significant negative correlation between ARGs and DRGs (P=0.0468).The study also highlighted the role of genetic determinants in biofilm formation, with all isolates possessing genes related to fimbriae production and adhesion, correlating with pronounced biofilm biomass production. NaOCl demonstrated considerable antimicrobial activity against these biofilms and planktonic cells. The minimum inhibitory concentration (MIC90) for planktonic bacterial cells was 0.125 mg/mL, while the minimal biofilm eradication concentration (MBEC90) ranged between 0.225 to 0.5 mg/mL. NaOCl demonstrated an MIC90 of 0.150 mg/mL (0.125-0.175 mg/mL) against planktonic C. albicans, while the MBEC90 was 0.250 mg/mL (0.200-0.500 mg/mL).These results highlight the challenge in treating biofilm-associated infections and underscore the potential of NaOCl as a robust antimicrobial agent against difficult-to-treat biofilm infections at concentrations lower than those typically found in commercial disinfectants.